2013
DOI: 10.4172/2155-6113.1000214
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Sleep Disturbance Related to Perceived Stress in Chinese HIVPositive Individuals: A Mixed Methods Study

Abstract: Background Few studies of HIV+ individuals in China have examined the associations between HIV-related stress with sleep disturbance and fatigue, which are common complaints among people living with HIV/AIDS (PLWHA). We carried out this study to examine the relationships among perceived stress, sleep disturbance, and fatigue in PLWHA in China. Methods A mixed methods study design was used during data collection in Shanghai, China, from December 2009 to March 2010. Qualitative in-depth interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Another limitation is the impossibility of establishing a temporal relation of cause and effect between the evaluated variables. On the other hand, the results found are supported by previous studies 8, [12][13][14]16,17 , strengthening this way the associations found. Furthermore, due to the scarcity of data on the topic addressed here and the current situation of the HIV epidemic, studies of this nature are fundamental to raise hypotheses and provide subsidies for other types of study 31 .…”
Section: Resultssupporting
confidence: 87%
“…Another limitation is the impossibility of establishing a temporal relation of cause and effect between the evaluated variables. On the other hand, the results found are supported by previous studies 8, [12][13][14]16,17 , strengthening this way the associations found. Furthermore, due to the scarcity of data on the topic addressed here and the current situation of the HIV epidemic, studies of this nature are fundamental to raise hypotheses and provide subsidies for other types of study 31 .…”
Section: Resultssupporting
confidence: 87%
“…For example, in 96 HIV+ individuals, the level of HIV trans-activator of transcription (tat) protein was significantly correlated with the circadian rhythm of systolic BP and with the Pittsburgh Quality Sleep Index and melatonin level [50•]. In addition, the heightened stress levels and disease-associated symptoms experienced by HIV+ individuals may lead to poor sleep quality and sleepdisordered breathing [74][75][76][77][78]. However, the effect of sleep quality on ABPM phenotypes in HIV+ individuals has not been evaluated.…”
Section: Sleepmentioning
confidence: 99%
“…Although treatment progress is significantly influential, it remains a source of stress for many people and is associated with an increase in the level of depression. Depression is one of the most common comorbidities in HIV infection, with a prevalence of 20-37% among people living with HIV or 3 times higher than the general population and the incidence of anxiety disorders around 20% (3)(4).…”
Section: Introductionmentioning
confidence: 99%